Failure to identify underlying autoimmunity and primary headache disorder might be the reasons for refractoriness of trochlear headaches. (28th August 2020) - Ojha, Pawan; Aglave, Vikram; Basak, Suranjana; Yadav, Jayendra
Introduction: A better understanding of etiology might improve poor outcomes of trochlear headaches (TRHs). Aims: To study clinical spectrum, etiology, and therapeutic response of TRH. Methods: Fifty-three TRH patients seen in a single center between 2015 and 2020 were included, excluding Trigeminal Autonomic Cephalalgia (TAC). Results: Mean age was 36.45 years (range 11–85 years), with 77.35% being females. Twenty-five patients had continuous trochlear headache (CTRH) and 28 episodic trochlear headache (ETRH). Tension-type headache (TTH) occurred in 9 ETRH patients and 24 of 25 CTRH patients, and migraine-like headaches occurred in 19 ETRH patients and 8 CTRH (trochlear migraine) patients. Prior history of headaches was noted in 22 of 28 ETRH and 11 of 25 CTRH patients. Twenty-eight responded to migraine/TTH prophylaxis, 25 being nonresponders (partial/no response). Fourteen of 25 nonresponders, 4 of 28 responders (4 of 4 secondary and 5 of 9 idiopathic trochleitis (IT), 3 of 9 primary TRH (PTRH), and 6 of 28 ETRH) had autoantibodies, that is, 11 antinuclear antibodies (ANAs) and 7 antithyroid antibodies. Ten of 14 (71.42%) antibody-positive nonresponders improved with immunosuppressants including steroids/hydroxychloroquine and only 11 required local injections. Finally, 38 patients had good response, 13 partial, and 2 no response. The etiology and refractoriness of IT can be attributed to underlying autoimmunity and a minor contribution by primary headaches, vice versa being the case for PTRH and ETRH. Refractory TRHs should be evaluated for underlying autoimmunity and primary headaches. Conclusion: Identification and treatment of underlying autoimmunity and primary headaches can help improve outcome of TRH.